Application for stay of proceedings and unconditional appearance [electronic resource] - 536802 Mohd. Fathel Laton (2012)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan)) - Universiti Teknologi Malaysia, 2012